The experiences of giving and receiving social support for men with localised prostate cancer and their partners - Kayleigh Nelson (ecancermedicalscience, 2019)
This study aimed to explore how men and their partners utilise social support in the first 12months following a localised prostate cancer diagnosis. Eighteen couples were recruited from two outpatient clinics following a localised prostate cancer diagnosis. Participants took part in semi-structured interviewsat three time-points following diagnosis. Thematic analysis revealed that support networks for couples became smaller as time progressed. Stigma was seen to have a role in men’s disclosure decisions. Partners generally provided higher levels of support than they received back. By Time 3, men who had previously attendedsocial support groups rejoined to seek informational and emotional support. For partners, there appeared to be a fine line between disclosing their true feelings and protecting their partner, and they appeared to struggle to access meaningful emotional support and accept instrumental support from trusted others. Further research is now needed to help identify which couples may benefit from professional encouragement to attend support groups and which couples may benefit from alternative support provision.